MOTIVATION OF SCIENTIFIC AND PEDAGOGICAL EMPLOYEES OF HIGHER EDUCATIONAL INSTITUTIONS AS A FUNCTION OF PERSONNEL MANAGEMENT - Ostapchuk, Tetiana; Biriuchenko, Svitlana; Borovska, Angelika (Social Economics, 2020)
In modern society, education is the key to the development not only of a person as a person, but also of the whole country. Education determines the future of society, that is, it forms a new mindset of citizens and acts as one of the means of managing the development of society. Stimulation of scientific and pedagogical workers of higher educational institutions is the main element that will allow to fully unleash their potential, thereby moving to a new higher level of educational services. The article considers and analyzes the essence of the incentive system and motivation of scientific and pedagogical staff. Modern forms and methods of material and intangible motivation of labor of workers in the sphere of higher education of Ukraine have been investigated, because motivation directly affects the level of efficiency of employees, which will make it possible to achieve significant changes in the education system. Three groups of factors of the material system of labor motivation with the distribution of wages in accordance with the established systems of remuneration, social benefits and income from activities are identified. It is proposed to divide intangible motivation into social and altruistic motives depending on the obtained social status and usefulness of work. The shortcomings in both material and intangible motivation of scientific and pedagogical staff are outlined. The level of salaries of scientific and pedagogical workers in Ukraine and developing countries was analyzed, respectively; a SWOT analysis was made on the basis of this. The relationship between the stimulation of scientific and pedagogical personnel and the system of allowances and surcharges, as well as effective indicators of the activities of higher educational institutions, is disclosed. On the basis of the study, the basic principles of managing the incentive system for scientific and pedagogical workers were identified. Problems in motivation of domestic personnel compared to foreign ones have been identified. It is indicated the removal of the state and the government from stimulating pedagogical workers and proposed to use the direction of intangible motivation of employees by universities.